Determinants of pelvic organ prolapse at public hospitals in Hawassa city, Southern Ethiopia, 2020: unmatched case control study - Bezabih Terefe Dora; Zemenu Yohannes Kassa; Nebiha Hadra; Bamlaku Birie Tsigie; Hawi Leul Esayas (BMC, 2022)
Abstract Introduction Even though the Pelvic organ prolapse (POP) is outstanding gynecologic problem, most private and asymptomatic nature of the illness makes it the "hidden epidemic." The aim of this study was to identify the determinants of POP. Methods Facility based unmatched case control study was conducted from June 15 to September 10, 2020. All cases diagnosed with POP were enrolled in the study by using consecutive random sampling method by assuming that patient flow by itself is random until the required sample size was obtained. Then 1:2 cases to control ratio was applied. A structured interviewer-administered questionnaire and chart review for type and degree of prolapse was used. Epi-data was used for data entry and SPSS were used for analysis. Chi square test and binary and multivariable logistic regression analysis was employed. Multicollinearity was checked. Result On multivariate logistic regression, heavy usual work load(AOR = 2.3, CI(1.066-4.951), number of pregnancy ≥ 5(AOR = 3.911, CI(1.108-13.802), birth space of < 2 years(AOR = 2.88, CI(1.146-7.232), history of fundal pressure (AOR = 5.312, CI(2.366-11.927) and history of induced labor (AOR = 4.436, CI(2.07-9.505) were significantly associated with POP with P value < 0.05 and 95% CI after adjusting for potential confounders. Conclusion Heavy usual work load, having pregnancy greater than five, short birth space, history of induced labor, and history of fundal pressure are independent predictors of pelvic organ prolapse. Hence the responsible body and obstetric care providers should counsel the women about child spacing, minimizing heavy usual work load and effect of multigravidity on POP. Incorporation of health education on those risk factors related to POP on antenatal and postnatal care should be considered. The obstetric care providers also avoid fundal pressure and labor induction without clear indication and favorability, and the hospital officials set a law to ban fundal pressure during labor.